PFAS Challenges and Novel Research: A Conversation With the Editorial Board of the AWWA Water Science Topical Collection on PFAS Analytics and Treatment. Issue 7 (1st September 2022) - Crimi, Michelle; Speth, Thomas F.; Chowdhury, Zaid K.; Dickenson, Eric R.V.; Knappe, Detlef R.U.; Liu, Jinxia
Key Takeaways: Per‐ and polyfluoroalkyl substances, "forever chemicals" commonly known as PFAS and used in countless products, have become a significant environmental and public health concern. Among especially alarming PFAS issues are their pervasive presence, the low concentrations at which they are found to be hazardous, and the challenges and limitations of remediation. A roundtable interview with water industry experts—guest editors of an AWWA Water Science article collection—presents their candid, comprehensive take on the PFAS picture.